Bio-inspired nano-traps for uranium extraction from seawater and recovery from nuclear waste - Qi Sun (Nature Portfolio, 2018)
Uranium extraction is important for both uranium recovery and nuclear waste management. Here, inspired by the high sensitivity of proteins towards specific metal ions, Ma and colleagues demonstrate that introducing secondary coordination spheres into amidoxime-functionalized porous polymers can enhance their uranyl chelating abilities.